To find the average rate of change, evaluate the function at the given points.
Evaluate the difference of the function at the given points.
Divide the difference of the function at the given points with the difference of the given points.
Answer:
1.89
Solution:
We have -44x - 86 = -3
First, we move the non x terms to the RHS of the equation. To do this, we add 86 to both sides.
Note: if a = b, then a + c = b + c
Therefore, -44x - 86 + 86 = -3 + 86
or, -44x = 83
Next, divide both sides by -44, which is the coefficent of x
Note: if a = b, then a ÷ c = b ÷ c
-44x
-44
=
83
-44
or, x = -1.89
Explaination:
This is right I guess
Answer:
120
Step-by-step explanation:
Step-by-step explanation:
1 Expand by distributing terms.
rx+r×2
2 Regroup terms.
rx+2r